Penerapan Media Gambar Seri Aktivitas Keluarga Berbasis Discovery Learning untuk Keterampilan Menulis Siswa SD - Wachdaniyah, Achla Inayatul; Purwati, Panca Dewi; Sabrina, Nazwa; Wibowo, Pasha Afriana; Febriyanto, Muhammad Zidan (Lembaga Yasin AlSys, 2025)
Although picture series media has been widely studied, research that specifically integrates the Family Activity Picture Series with the Discovery Learning model for lower-grade students remains limited. This study aims to describe the implementation of this medium and to analyze its contribution to improving the simple sentence writing skills of second-grade students. The study employs a mixed-methods approach with a Sequential Exploratory design and involves 18 students as research participants. Data were collected through observation, documentation, and learning outcome tests, then analyzed through data reduction, data display, conclusion drawing, and the calculation of scores and achievement categories. The results indicate that the learning process was effective, with an average score of 10.83 out of 12 and 77.8% of students achieving the “Very Good” category, so that the application of picture series media based on Discovery Learning was proven to improve students’ simple sentence writing skills. These findings enrich theoretical discourse on the effectiveness of visual media in language learning and provide practical implications for teachers in designing instructional strategies that support the development of early writing skills among lower-grade students.